EVALUATION OF THE FREEZABILITY OF THE BOVINE EPIDIDYMIS TAIL SPERM WITH THE ADDITION OF ANTIOXIDANTS - Cruz, Gabriela Passamani da; Zanfrilli dos Santos, Ana Paula; Freitas Guaitolini, Carlos Renato de; Denck Tramontin, Marcio Luiz; Rigoto, Renata Patricia; Crespilho, Andre Maciel; Freitas Dell'Aqua, Camila de Paula [UNESP]; Mello Martins, Maria Isabel; Marques, Ana Beatriz; Tsunokawa Hidalgo, Myrian Megumy; Oliveira Sestari, Danielle Andressa; Magalhales, Ricardo; et al. (Cryo Letters, 2021)
BACKGROUND: The cryopreservation and recovery of epididymis tail sperm is an important biotechnology dependent on the composition of the freezing medium. OBJETIVE: To evaluate the effect of melatonin, added to commercial freezing medium extender, on the kinetics and viability of bovine epididymis tail sperm. MATERIAL AND METHODS: Five routines were performed, each consisting of eight epididymis and the structures were sliced onto a glass plate containing a commercial diluting medium for Botubov (R). The samples were divided into four groups, with 80 x 10(6) spermatozoa per mL. Group 1: samples diluted in Botubov (R). Group 2: samples centrifuged (600 g, 10 min), and the pellet re-suspended in Botubov (R). Group 3, samples diluted in Botubov (R) containing 100 pM melatonin. Group 4: samples centrifuged (600 g, 10 min) and the pellet resuspended in Botubov (R) with 100 pM melatonin. The samples were transferred to 0.5 mL straws at 40 x 10(6) viable spermatozoa, stabilized at 5 degrees C for 4 h, transferred to liquid nitrogen vapour for 20 min, dipped in liquid nitrogen and stored in a cryogenic cylinder. After thawing (46 degrees C, 15 s), sperm kinetics and viability parameters were evaluated. RESULTS: There was no difference in the parameters of total motility (MT, %), progressive motility (MP, %), progressive linear velocity (VSL, mu m/s), curvilinear velocity (VCL, mu m/s), linearity (LIN, %), spermatozoa with rapid movement (RAP, %) and level of intact plasma membranes and acrosome (IPMA, %) among the groups studied. However, a difference was observed between the routines performed. CONCLUSION: The protocol for freezing bovine epididymis tail sperm is applicable; however, there is an influence of the epididymis used, for the best efficacy of this biotechnology.
Keywords: bovine epididymis; freezing; melatonin; spermatic parameters